ANALISIS ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY UNTUK MENGUKUR TERJADINYA JANUARI EFFECT PADA KELOMPOK SAHAM INDEKS LQ 45 DI BEI - ERVIVA FARIANTIN; ELVINA SETIAWATI; ULFIYANI ASDIANSYURI (GANEC SWARA, 2024)
The purpose of this study was to determine the differences in market reactions that occurred in January with other months. If there is a difference, the January Effect occurs in the Indonesian capital market, especially for companies included in the LQ45 Index, and vice versa. The variables used to view market reactions in this study are abnormal return and trading volume activity. This research uses historical stock data monthly. The analytical tool used in this study is Paired sample t-test and Wilcoxon Sign Test. The results of the research analysis showed that in terms of abnormal returns there were no significant differences, with a significance value greater than 0.05 so that it could be said that there was no January effect phenomenon in the LQ45 Index stock group on the Indonesia Stock Exchange, which was calculated by paired sample t-test. test, as well as in terms of trading volume activity, the January Effect did not occur on the LQ 45 Index stock group on the Indonesia Stock Exchange calculated by the Wilcoxon Sign Test, this shows that there was no January Effect anomaly in the Indonesian capital market